Physics meets philosophy at the Planck scale : contemporary theories in quantum gravity - Callender, Craig, 1968-; Huggett, Nick (Cambridge University Press, 2001)
Collects classic and original contributions from leading experts to discuss one of the greatest challenges in fundamental physics: how quantum mechanics and general relativity can be reconciled in a theory of 'quantum gravity'. A key topic of debate and collaboration between physicists and philosophers.